Types of Plots in Khaled Hosseini's The Kite Runner - Uswatul Chaira; Yuniarti Yuniarti (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2020)
This study discusses the types of plot used by Khaled Hosseini in his novel “The Kite Runner”. Plot is an element in a novel which is necessary in order to understand the storyline of the novel. The study was a descriptive study. The results showed that the plots found in The Kite Runner included maturation, escape, rescue, love, revenge, the riddle, quest, underdog, sacrifice, ascension and rivalry.